Some Recent Studies on the Iranian Religions - Gray, Louis H. (Harvard theological review, 1922)
It is curious, and perhaps significant, that the two most important volumes on the Iranian religions which have appeared within the last decade should have been written by scholars who were not professed Iranists. Professor James Hope Moulton, the author of the Hibbert Lectures on Early Zoroastrianism (London, 1913), was a theologian and a hellenist; Professor Raffaele Pettazzoni, who has just given us his La Religione di Zarathustra (Bologna, 1920), is a student of comparative religion of the finest and sanest type. Pettazzoni seems not to have had the advantage of consulting Moulton's volume; but while from one point of view this may be regrettable, from another it has worked for good, since two scholars have reached independently results which, when combined, put the genesis of Iranism in an entirely new light and go far toward the solution of many perplexing problems, if, indeed, they may not have solved the riddle as a whole. Of Moulton's work I have expressed an opinion elsewhere, and subsequent reflection has only confirmed that judgement.